O efeito da videoconferência sobre a aprendizagemna educação a distância : uma investigação quantitativa - Mendes, André Cruz (2014)
In the last decade, DL (Distance Learning) has expanded exponentially. This growth is due to the evolution of the Internet, which has allowed the airing of long distance digital learning materials as well as the fulfillment of several online interactive activities. In this context, a videoconference system consists in a form of video synchronous transmission between several people for conversation. However, it should be noted that the terms "video" and "videoconference" can be used flexibly, with various meanings. So, initially this paper proposes a video taxonomy to define and conceptualize the researched object, which is the videoconference, and it shows that this technology is interesting for the DL, because the discussions held by it approach the reality of a classroom. Currently, there are proper low-cost applications for videoconferencing via internet compatible with many systems, which make it feasible for the DL. Thus, many organizations may choose to use videoconferencing software to improve the education quality. Nonetheless, it is necessary to know if this kind of software is indeed effective when used for that purpose. To do so, the present research has implemented systematic mappings in search of articles that have examined this issue with a quantitative research methodology. The results of such mappings, however, showed a lack of this kind of research. Furthermore, the studies found which sought to follow that experimental design were inconclusive due to missing data. Some even contain validity failures. Therefore, there was a need to revise research methods and important measurement concepts that are considered in the evaluation of learning. To this end, this master thesis presents that review and proposes a construction technique of tests for learning assessment (BLIRT), which has as base the taxonomy of Bloom and IRT (Item Response Theory). Along with these subsidies, instruments were built and used in an experiment with 750 subjects to evaluate the effectiveness of a videoconference system regarding the learning in the context of the DL. Hence, this research follows an experimental design involving comparison between groups.